ANALISIS PERILAKU, KOMPETENSI, DAN MOTIVASI ORGANISATIONAL CITIZENSHIP TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN PROPERTI DI KOTA BATAM - Wasiman, Wasiman; Wangdra, Yvonne; Effendi, Syahril (Universitas Putera Batam, 2024)
This research aims to explore the impact of Organizational Citizenship Behavior (OCB), competence, and motivation on the performance of employees in property companies in Batam City. It also seeks to measure the extent of the influence of these variables through regression analysis, as well as the outcomes of t-tests and f-tests. The study originated from a survey that highlighted various complaints regarding OCB, competence, and motivation within these companies, prompting the researchers to investigate the issue further. The methodology involved conducting a survey and distributing questionnaires to 10 property companies in Batam City, deemed representative for the study. A total of 125 respondents were sampled, and several tests were conducted, including validity, reliability, regression, normality, t-test, and f-test. The validity test results indicated that all variables and statements were valid, while the reliability test confirmed the reliability of all statements. The analysis concluded that OCB, competence, and motivation significantly affect employee performance. Both the t-test and f-test results also demonstrated a significant impact on employee performance. The R-squared test results revealed that 81% of the variance in employee performance could be explained by the independent variables.